2014
DOI: 10.1021/jp502882j
|View full text |Cite
|
Sign up to set email alerts
|

Yb3+ Ions Distribution in YAG Nanoceramics Analyzed by Both Optical and TEM-EDX Techniques

Abstract: We show the approach in the structural and spectroscopic analysis of Yb3+-doped YAG nanoceramics prepared using the low temperature-high pressure sintering technique (LTHP) by conjugation of both TEM-EDX and optical techniques. Pressure sintering dependences of absorption, emission, and decays are analyzed and interpreted. The sample pressurized at 8 GPa for sintering is characterized by the highest transparency and confirms the Y3Al5O12 garnet structure of the grains of ∼21 nm average size. Yb3+ ion distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…Further studies, involving high-resolution scanning TEM analysis, would be required to conrm this suggestion. 51 (3) The presence of Ce 4+ ions, that could act as luminescence quenchers through energy transfer from Ce 3+ to Ce 4+ . 52,53 Bulk YAG:Ce overcome an annealing under reducing atmosphere to force cerium ions into their 3+ state.…”
Section: Optical Properties Of Nano-yag:cementioning
confidence: 99%
“…Further studies, involving high-resolution scanning TEM analysis, would be required to conrm this suggestion. 51 (3) The presence of Ce 4+ ions, that could act as luminescence quenchers through energy transfer from Ce 3+ to Ce 4+ . 52,53 Bulk YAG:Ce overcome an annealing under reducing atmosphere to force cerium ions into their 3+ state.…”
Section: Optical Properties Of Nano-yag:cementioning
confidence: 99%
“…There has been only very few reports of highly transparent nanocrystalline ceramic until the recent work on silicate garnets fabricated by direct conversion from bulk glass starting material in mutianvil high-pressure apparatus 16 . Nevertheless, all these processes require high-pressure and high-temperature sintering conditions, and it remains challenging to reach industrial production due to complex processes and reproducibility problems 1618 . Ikesue et al 19 reported the possibility to prepare transparent YAG ceramics by pressureless slip casting and vacuum sintering at about 1800 °C but with large grain size (40–60 μm).…”
Section: Introductionmentioning
confidence: 99%
“…Ikesue et al 19 reported the possibility to prepare transparent YAG ceramics by pressureless slip casting and vacuum sintering at about 1800 °C but with large grain size (40–60 μm). However, even though fully densified ceramics with nanometer-scale grain sizes are promised to unprecedented optical, mechanical and electrical properties with applications in lasers, phosphors, and electrical devices 1,13,20,21 , pressureless fabrication of transparent nanoceramics has never been reported up to date.…”
Section: Introductionmentioning
confidence: 99%
“…The second origin of nonradiative transitions is related to effects at the particle surface. Due to the fact that the surface of materials is often strongly defected, the spectroscopic properties of ions on the surface may differ from their counterparts in the bulk part of the material 53 55 . The degree of surface ion contribution to the total emission spectrum changes with size and is more prominent in nanocrystals 14 .…”
Section: Introductionmentioning
confidence: 99%